TOXICITY AND HAEMATOLOGICAL CHANGES OF Datura innoxia STEM ON Clarias gariepinus JUVENILES - Maimuna, A.; Isiyaku, Mohammed Sani; Laurat, H. T.; Iorhiin, R. M.; Shaibu, A. L. (FUDMA JOURNAL OF SCIENCES, 2024)
The acute toxicity and haematological changes of Datura innoxia stem on Clarias gariepinus juveniles was investigated in a static bioassay to determine the Median Lethal concentrations (LC50) at 96 hrs of exposure. Six graded concentrations of 0, 320, 330,340, 350 and 360mg/l of the aqueous extract were applied to C. gariepinus juveniles in plastic bowls. The result obtained revealed the 96hrs LC50 values to be 86.67mg/l with an 87% confidence interval between the lower and higher limits of 320 and 360mg/l. Fish exposed to acute toxicity test exhibited several abnormal behaviours, including air gulping/gasping, erratic swimming, discolouration haemorrhage, loss of reflex and molting were observed at the bottom of the bowl just before death The oxygen consumption by juveniles decreased with increased concentrations of Datura innoxia stem extract. The packed cell volume (31.34-34.78%), the red blood cell counts (1.75-2.01), haemoglobin (9.03-11.12g/dl) and mean corpuscular haemoglobin concentration were significantly depleted while, white blood cell counts (6.05-7.21) significantly decreases as the concentrations of Datura innoxia stem extract increases. The implication of these findings revealed that the stem of D. innoxia stem have negative effects on the test fish. The toxic effect of Datura innoxia stem on Clarias gariepinus juveniles were both time (12hrs) and dose dependent (340mg/l). It was concluded that Datura innoxia stem are harmful to Clarias gariepinus juveniles with significant haematological alterations.